The impact of tobacco chemicals and nicotine on placental development. (11th February 2020) - Suter, Melissa A.; Aagaard, Kjersti M.
Abstract: Despite decades of messages warning about the dangers of tobacco use in pregnancy, 10% to 15% of pregnant women continue to smoke. Furthermore, an increased popularity of electronic nicotine delivery systems (ENDS) over the past decade in women of childbearing age raises parallel concerns regarding the effects of vaporized nicotine use in pregnancy. While research using animal models which mimic tobacco smoke and nicotine exposure in pregnancy have largely replicated findings in humans, few studies focus directly on the effects of these exposures on the placenta. Because the placenta is a fetal derived tissue, and nicotine and other components of tobacco smoke are either processed by or transported directly through the placenta, such studies help us understand the risks of these exposures on the developing fetus. In this review, we summarize research on the placenta and placental‐derived cells examining either tobacco smoke or nicotine exposure, including both histologic and subcellular (ie, epigenetic and molecular) modifications. Collectively, these studies reveal that tobacco and nicotine exposure are accompanied by some common and several unique molecular and epigenomic placental modifications. Consideration of the nature and sequelae of these molecular mediators of risk may help to better inform the public and more effectively curtail modifiable behavior.